(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The role of power and thermal energy is impossible to overestimate in development of both state economy sector and everyday life of households. Importance is connected with use of resources, economical feasibility and effect to climate changes. The optimization of energy production allows to promote development of sustainable society. The most popular and efficient technologies for generation of power and thermal energy are cogeneration plants (CHP). Traditional evaluation methodologies of energy production systems are based on analysis of energy and mass balances as well as on cost analysis. It is not enough for assessment of complete sustainability of system. Necessary environmental impact assessment of energy production is possible to implement by use of emergy analysis. Definition of emergy includes one type of energy, which is used directly or indirectly to produce materials, provide services and finances. Emergy dimension is emjoules (seJ.). Paper presents case study of emergy analysis of different operation modes of one cogeneration plant.